Osterix represses adipogenesis by negatively regulating PPARγ transcriptional activity - Han, Younho (Sci Rep, 2016)
Osterix is a novel bone-related transcription factor involved in osteoblast differentiation, and bone maturation. Because a reciprocal relationship exists between adipocyte and osteoblast differentiation of bone marrow derived mesenchymal stem cells, we hypothesized that Osterix might have a role in adipogenesis. Ablation of Osterix enhanced adipogenesis in 3T3-L1 cells, whereas overexpression suppressed this process and inhibited the expression of adipogenic markers including CCAAT/enhancer-binding protein alpha (C/EBPα) and peroxisome proliferator-activated receptor gamma (PPARγ). Further studies indicated that Osterix significantly decreased PPARγ-induced transcriptional activity. Using co-immunoprecipitation and GST-pull down analysis, we found that Osterix directly interacts with PPARγ. The ligand-binding domain (LBD) of PPARγ was responsible for this interaction, which was followed by repression of PPARγ-induced transcriptional activity, even in the presence of rosiglitazone. Taken together, we identified the Osterix has an important regulatory role on PPARγ activity, which contributed to the mechanism of adipogenesis.